2020
DOI: 10.1108/ijppm-06-2020-0298
|View full text |Cite
|
Sign up to set email alerts
|

Appropriation of sustainability priorities to gain strategic advantage in a supply chain

Abstract: PurposeThe authors develop a methodology to select appropriate sustainable supply chain indicators (SSCIs) to measure Sustainable Development Goals (SDGs) in the global supply chain.Design/methodology/approachSSCIs are identified by reviewing the extant literature and topic modeling. Further, they are evaluated based on existing SDGs and ranked using the fuzzy technique for order preference by similarity to ideal solution (TOPSIS) method. Notably, the evaluation of indicators is a multi-criteria decision-makin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 129 publications
0
27
0
Order By: Relevance
“…SCMP defines approaches and practices that best connect vendors, retailers, dealers, and even customers to meet the lengthy success goals for the firm's performance. The systematic literature review found that there is a relationship between SCMP and industry performance success (Kumar et al, 2020). According to Fekpe and Fiagbey (2021), that knowledge exchange is an essential factor for process sustainability, and it could be done with the help of quality and level of information technology because it allows a company to react quickly to evolving customer demands.…”
Section: Literature Reviewmentioning
confidence: 99%
“…SCMP defines approaches and practices that best connect vendors, retailers, dealers, and even customers to meet the lengthy success goals for the firm's performance. The systematic literature review found that there is a relationship between SCMP and industry performance success (Kumar et al, 2020). According to Fekpe and Fiagbey (2021), that knowledge exchange is an essential factor for process sustainability, and it could be done with the help of quality and level of information technology because it allows a company to react quickly to evolving customer demands.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Table 6 summarizes the papers reviewed in this category, highlighting the methodological approaches and contexts of application of MCDM methods [60][61][62][63][64][65][66][67][68][69][70][71][72].…”
Section: Multiple Sustainable Development Goalsmentioning
confidence: 99%
“…In this category, most of the studies adopted compromise methods (TOPSIS and VIKOR, for example) [61,63,64,66,[69][70][71], whereas three employed a utility-based method (AHP) [62,64,65], two applied an outranking method (PROMETHEE) [68,69], and the remaining studies [60,67,71,72] used multi-objective methods (e.g., GP and MOLP). Finally, it should be emphasized that four studies [61,64,69,70] combined fuzzy logic with MCDM methods, and one of them [65] employed artificial intelligence algorithms (i.e., Bacterial Foraging Optimization Algorithm and the Firefly Algorithm) to optimize objective functions for the intelligent allocation of energy to different contributors to surface water treatment plants in India.…”
Section: Multiple Sustainable Development Goalsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, the manufacturing industry has undergone a substantial process of transformation, in order to cope with the needs of the digitalization of production processes imposed by the advent of Industry 4.0 (Ali and Aboelmaged, 2021; Frederico et al. , 2021) and the challenge of sustainability (Bag et al , 2021; Kumar et al. , 2020).…”
Section: Introductionmentioning
confidence: 99%